(untitled) (Research, Society and Development, 2020)
Interpersonal conflicts are present in the relationships of the elderly in different social contexts. The objective of the present study is to analyze the evidence available in the literature on the interpersonal conflicts of the elderly. This is an integrative literature review, carried out in the Latin American and Caribbean Health Sciences (LILACS), National Library of Medicine, National Institutes of Health (Pubmed) and Cumulative Index of Nursing and Allied Health (CINAHL) databases, in the month of December 2019. Primary studies were included that addressed conflicts of the elderly, published in Portuguese, English or Spanish, available in full online, without temporal cut. After applying the inclusion and exclusion criteria, 13 articles were selected for analysis. The results report the presence of elderly conflicts related to their lifestyle, choices, self-care, dependence, health, differences of opinion, marital or financial discord, lack of support and breach of expectations. In Long-Term Care Institutions, conflicts are related to sadness, verbal aggressions and disputes over objects or spaces. Still, high priority mountains to face problems such as loyalty, low negativity and constructive approach. It is concluded that, in general, the suppression of the elderly’s autonomy is related to most conflicts.